ANALISIS KEBERHASILAN BELAJAR MAHASISWA PENERIMA BEASISWA DI IAIN PURWOKERTO MENGGUNAKAN REGRESI LOGISTIK - Mutijah Mutijah (Jurnal Penelitian Agama, 2016)
Abstract: The results of data analysis showed that disadvantaged-students scholarship and Bidik Misi scholarship recipients succeed in his studies indicated arnaverage IP obtained was 3.43 with details of 5.6% of the students received a designation of high academic ability and 94.4% received a designation capability extremely high academic. Meanwhile, scholarship recipients of non-disadvantaged-students and non-Bidik Misi scholarship have lower IP acquisition anaverage of 3.29 to 8.4% student predicate academic ability is low, 5.6% high, and very high 86.0%. There's no influence of economic factors of students with learning success, there is no effect between the origin of SMA / MA SMK to the success of learning, and there is influence between public or private schools of origin against the learning success. Keywords: Scholarship, Poor, Economic Factors.